Improving the diagnosis of LV non-compaction with cardiac magnetic resonance imaging. (15th February 2015) - Choudhary, P.; Hsu, C.J.; Grieve, S.; Smillie, C.; Singarayar, S.; Semsarian, C.; Richmond, D.; Muthurangu, V.; Celermajer, D.S.; Puranik, R.
Abstract: Background: Current diagnostic criteria for left ventricular non-compaction (LVNC) poorly correlate with clinical outcomes. We aimed to develop a cardiac magnetic resonance (CMR) based semi-automated technique for quantification of non-compacted (NC) and compacted (C) masses and to ascertain their relationships to global and regional LV function. Methods: We analysed CMR data from 30 adults with isolated LVNC and 20 controls. NC and C masses were measured using relative signal intensities of myocardium and blood pool. Global and regional LVNC masses was calculated and correlated with both global and regional LV systolic function as well as occurrence of arrhythmia. Results: LVNC patients had significantly higher end-systolic (ES) and end-diastolic (ED) NC:C ratios compared to controls (ES 0.21 [SD 0.09] vs. 0.12 [SD 0.02], p < 0.001; ED 0.39 [SD 0.08] vs. 0.26 [SD 0.05], p < 0.001). NC:C ratios correlated inversely with global ejection fraction, with a stronger correlation in ES vs. ED (r = − 0.58, p < 0.001 vs. r = − 0.30, p = 0.03). ES basal, mid and apical NC:C ratios also showed a significant inverse correlation with global LV ejection fraction (ES basal r = − 0.29, p = 0.04; mid-ventricular r = − 0.50, p < 0.001 and apical r = − 0.71, p < 0.001). Upon ROC testing, an ES NC:C ratio of 0.16 had a sensitivity of 70% and a specificity of 95% for detection of significant LVNC. Patients with sustained ventricular tachycardia had a significantly higher ES NC:C ratio (0.31 [SD 0.18] vs. 0.20 [SD 0.06], p = 0.02). Conclusions: The NC:C ratio derived from relative signal intensities of myocardium and blood pool improves the ability to detect clinically relevant NC compared to previous CMR techniques.